2006
DOI: 10.1177/009286150604000104
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the US Regulatory Environment for Drug-Device and Biologic-Device Combination Products

Abstract: The Food and Drug Administmtion (FDA) has for many years focused and identified its mission regarding medid products on tmditional dasses and uses for products. This legacy has contributed to a sometimes-confusing set of praiwct dassification precedents that are not alwajs s t r m g h q d or logid for the advanad ptwducts under development. complicating this jbrther is the fact that, although one FDA center may have histm'd responsibility or legal jurisMichael R. Hamrell, PhD, RAC Yorba Linda, California Presi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This review has demonstrated that the regulation of these products is extremely complex, which confirms the views of other commenters. 14,15 Each jurisdiction has its own regulatory framework with different legislation. Furthermore, there is a range of regulatory authorities involved, which adds to the complexity of the process.…”
Section: Discussionmentioning
confidence: 99%
“…This review has demonstrated that the regulation of these products is extremely complex, which confirms the views of other commenters. 14,15 Each jurisdiction has its own regulatory framework with different legislation. Furthermore, there is a range of regulatory authorities involved, which adds to the complexity of the process.…”
Section: Discussionmentioning
confidence: 99%
“…Three FDA centers regulate combination products: 'Biologics Evaluation and Research' (CBER), 'Devices and Radiological Health' (CDRH), and 'Drug Evaluation and Research' (CDER) [83]. Determining which center has jurisdiction is a major challenge, as many of the new products being developed do not fit neatly into existing regulatory categories.…”
Section: Regulatory Issuesmentioning
confidence: 99%
“…The MDD process has been satisfactorily described in literature; however, there is a lack of comprehensive models that would support design teams with different experiences and backgrounds. In general, published studies in this area either address the MDD with a specific focus on regulations (9,13,14) or provide proposals for various approaches to MDD (9,15,16).…”
Section: Introductionmentioning
confidence: 99%